Regenerative medicine in urology: the future of urinary reconstruction. Issue 2 (29th April 2020) - Harris, Kelly; Bivalacqua, Trinity J
Abstract : Tissue engineering and regenerative technology are at the cutting edge in reconstructive urology today. However, despite the advances, there are still challenges to be overcome and novel ideas to be investigated.